A method for screening tigecycline-resistant gene tet(X) from human gut. (March 2021) - Zeng, Yu; Lu, Jiayue; Liu, Congcong; Ling, Zhuoren; Sun, Qiaoling; Wang, Hanyu; Zhou, Hongwei; Hu, Yanyan; Chen, Gongxiang; Zhang, Rong
Highlights: A targeted screening method was performed on human gut. Tigecycline-resistant aerobic or facultative anaerobic isolates were recovered. There was a higher prevalence rate of tet (X4) compared to previous reports. This is a specific screening strategy to develop knowledge of tet (X). Abstract: Objectives: To develop an effective enrichment method for tet (X) detection, we performed PCR and Sanger sequencing to screen and confirm the presence of tet (X) gene. Methods: Species were identified by MALDI-TOF MS analysis. The minimum inhibitory concentrations (MICs) of common antibiotics were determined by broth microdilution and interpreted according to the CLSI guidelines and EUCAST breakpoints. Results: We obtained 29 (2.26%, 29/1284) tet (X4)-positive Escherichia coli, and 96.6% of those (28 isolates) exhibited resistance to tigecycline. Conclusion: This specific screening strategy for functional tet (X) mediating tigecycline resistance will be useful to facilitate development and advancement of our knowledge of tet (X).